Relation between cost of drug treatment and body mass index in people with type 2 diabetes in Latin America - Elgart, Jorge Federico (2017)
Despite the frequent association of obesity with type 2 diabetes (T2D), the effect of the former on the cost of drug treatment of the latest has not been specifically addressed. We studied the association of overweight/obesity on the cost of drug treatment of hyperglycemia, hypertension and dyslipidemia in a population with T2D.